Ammonium intensifies CAM photosynthesis and counteracts drought effects by increasing malate transport and antioxidant capacity in Guzmania monostachia - Pereira, P; Gaspar, M; Smith, J; Mercier, H (Oxford University Press, 2018)
Guzmania monostachia (Bromeliaceae) is a tropical epiphyte capable of up-regulating crassulacean acid metabolism (CAM) in its photosynthetic tissues in response to changing nutrient and water availability. Previous studies have shown that under drought there is a gradient of increasing CAM expression from the basal (youngest) to the apical (oldest) portion of the leaves, and additionally that nitrogen deficiency can further increase CAM intensity in the leaf apex of this bromeliad. The present study investigated the inter-relationships between nitrogen source (nitrate and/or ammonium) and water deficit in regulating CAM expression in G. monostachia leaves. The highest CAM activity was observed under ammonium nutrition in combination with water deficit. This was associated with enhanced activity of the key enzyme phosphoenolpyruvate carboxylase, elevated rates of ATP- and PPi-dependent proton transport at the vacuolar membrane in the presence of malate, and increased transcript levels of the vacuolar malate channel-encoding gene, ALMT. Water deficit was consistently associated with higher levels of total soluble sugars, which were maximal under ammonium nutrition, as were the activities of several antioxidant enzymes (superoxide dismutase, catalase, ascorbate peroxidase, and glutathione reductase). Thus, ammonium nutrition, whilst associated with the highest degree of CAM induction in G. monostachia, also mitigates the effects of water deficit by osmotic adjustment and can limit oxidative damage in the leaves of this bromeliad under conditions that may be typical of its epiphytic habitat.